Contact lenses for ophthalmic drug delivery. (September 2017) - Hui, Alex
Abstract : Contact lenses as a means to deliver pharmaceuticals to the eye have seen a significant increase in research interest in the past few years. This review will detail the in vitro experiments which have investigated use of these contact lenses in the context of the desired pharmacological treatment goals in the management of infectious, inflammatory, allergic and glaucomatous diseases of the eye. The techniques researchers have employed to modify and tailor drug release rates from these materials, including the use of vitamin E diffusion barriers, modified ionicity, molecular imprinting and incorporation of drug reservoirs, will be discussed, as well as their impact on drug release kinetics. Finally, the demonstration of the feasibility of these materials when applied in vivo in animal models as well as in humans with and without disease will be presented and their results discussed relating to their implications for the future of the field.